Peuplement colonisateur au XVIIIe siècle dans le gouvernement du Québec - Mathieu, Jacques; Béland, François; Jean, Michèle; Larouche, Jeannette; Lessard, Renald (Man and Nature / L'homme et la nature)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 1984)
This article studies some of the factors which influenced rural resettlement in eighteenth-century Quebec: economic conditions, laws of inheritance, family size, marriage customs, the attitudes of the seigneurs, the presence of family members in newly-settled areas. The relative importance of each factor varied considerably at different times and in different places.